1971
DOI: 10.1128/jvi.7.6.813-820.1971
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Thymidine Kinase to Thymidine Kinaseless L Cells by Infection with Ultraviolet-Irradiated Herpes Simplex Virus

Abstract: L cells lacking thymidine kinase (TK) activity (Ltk-cells) have been stably transformed to a TK-positive phenotype by infection with ultraviolet-irradiated herpes simplex virus (HSV-UV). The highest frequency of the Ltkto Ltk+ transformation observed in these experiments was approximately 10-3, whereas no measurable transformation was observed (less than 10-8) in the absence of HSV-UV infection. Cell lines of HSV-transformed Ltk+ cell lines contain 7 to 24 times as much TK activity as do the parental Ltk-cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…One of the first and most convincing studies demonstrated the permanent transfer of genetic information to code for virus enzyme and virus antigen. Davis et al (1974) and Munyon et al (1971; demonstrated that mouse L-cells deficient in the enzyme thymidine kinase can be converted to a positive thymidine kinase phenotype by means of HSV-1 which had been inactivated with ultraviolet light; the new thymidine kinase in the cells has the distinct properties characteristic of the herpesvirus type used to infect the cells (Ogino and Rapp, 1971). Furthermore, the viral DNA coding for the TK enzyme remains stably associated with the cells' progeny and DNA fragments of approximately 10% of the HSV genome can be detected with DNA:DNA hybridization (D. Kingsbury, 1974, personal communication).…”
mentioning
confidence: 99%
“…One of the first and most convincing studies demonstrated the permanent transfer of genetic information to code for virus enzyme and virus antigen. Davis et al (1974) and Munyon et al (1971; demonstrated that mouse L-cells deficient in the enzyme thymidine kinase can be converted to a positive thymidine kinase phenotype by means of HSV-1 which had been inactivated with ultraviolet light; the new thymidine kinase in the cells has the distinct properties characteristic of the herpesvirus type used to infect the cells (Ogino and Rapp, 1971). Furthermore, the viral DNA coding for the TK enzyme remains stably associated with the cells' progeny and DNA fragments of approximately 10% of the HSV genome can be detected with DNA:DNA hybridization (D. Kingsbury, 1974, personal communication).…”
mentioning
confidence: 99%
“…Candidate plasmids were cleaved with restriction nucleases and analyzed by electrophoresis in 1 % agarose gels to verify that they contained both pAGO and SV40 DNAs. After cleavage by Cla I, the candidate plasmids were also utilized to biochemically transform LM(TK-) cells to TK+ in order to show that they contained a functional TK gene (Bacchetti and Graham, 1977;Kit et al, 1980~;Munyon et al, 1971;.…”
Section: Preparation Of Cellular Viral and Plasmid D N Amentioning
confidence: 99%
“…We have used a quantitative assay for herpesvirus transformation (Rapp and Buss, 1975/76; Rapp and Turner, 1978). Because HSV carries its own TK, the "biochemical transformation" of TK-cells by virus TK allows growth of the transformed cells in selective medium which kills the remaining TKcells (Littlefield, 1965;Munyon et al, 1971;Davis et al, 1974;Rapp and Buss, 1975/76). Transformation assays were carried out using the selective medium described by .…”
Section: Transformation Assaymentioning
confidence: 99%